2009
DOI: 10.1044/0161-1461(2008/08-0009)
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Morphological Awareness Intervention as a Tool for Improving Literacy

Abstract: Practitioners should consider the likely benefits of literacy intervention that focuses on developing morphological awareness in conjunction with other types of linguistic awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 10 publications
(6 reference statements)
6
76
0
8
Order By: Relevance
“…Although this number is larger than that identified by Reed (2008), there is clearly need for more studies particularly across age and ability levels. Second, with respect to research design, there were a number of examples of random assignment of individuals to instructional conditions (Abbott & Berninger, 1999;Berninger et al, 2003;Berninger et al, 2008;Kirk & Gillon, 2009;Lyster, 1998Lyster, , 2002Tyler et al, 2003), though many of the other investigators did manage to randomly assign classes. Given that most studies saw morphological instruction as a part of regular classroom instruction and that the instruction usually took place over several weeks or more, the proportion of studies with random assignment of individuals seems reasonable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this number is larger than that identified by Reed (2008), there is clearly need for more studies particularly across age and ability levels. Second, with respect to research design, there were a number of examples of random assignment of individuals to instructional conditions (Abbott & Berninger, 1999;Berninger et al, 2003;Berninger et al, 2008;Kirk & Gillon, 2009;Lyster, 1998Lyster, , 2002Tyler et al, 2003), though many of the other investigators did manage to randomly assign classes. Given that most studies saw morphological instruction as a part of regular classroom instruction and that the instruction usually took place over several weeks or more, the proportion of studies with random assignment of individuals seems reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…The metaanalysis described here synthesizes results from morphological interventions that have examined the effect of instruction both with participants identified with reading difficulties (e.g., Arnbak & Elbro, 2000;Tyler, Lewis, Haskill, & Tolbert, 2003) and spelling difficulties (e.g., Kirk & Gillon, 2009) and with undifferentiated participants (e.g., Baumann et al, 2002;Baumann et al, 2003;Bowers & Kirby, 2006, in press). We investigate results from instructional studies with age groups from preschool (e.g., Lyster, 1998Lyster, , 2002 to upper elementary (e.g., Robinson & Hesse, 1981) and across a variety of languages (English, Danish, Dutch, and Norwegian).…”
Section: Current Morphological Instruction Researchmentioning
confidence: 99%
“…A study by De Graaff [38] concluded phonemic segmentation skills improved, not by performing phonemic awareness listening tasks, but by practicing reading. Kirk and Gillon [67] reported it was not children's phonemic awareness knowledge which was the factor in reading achievement. Instead, the use of highly structured and scaffolded spelling-patterns most impacted children's success in learning to read.…”
Section: Phonemic Awareness Instructionmentioning
confidence: 99%
“…Phonemic awareness is defined by the National Reading Panel as "the ability to focus on and manipulate phonemes in spoken words" ( [8], p. 2-1). Phonemic awareness teaching approaches often do not involve print, and most often include phonemic segmentation tasks [8] [29] [31] [67]. For instance, children listen to a spoken word "cat", and then children are asked to segment the spoken word into separate speech sounds /c/, /a/, /t/ [31].…”
Section: Phonemic Awareness Instructionmentioning
confidence: 99%
“…Medvetenhet om morfem har tydliga och positiva effekter på barns ordavkodning och stavning (Kirk & Gillon, 2009;Wolter, Wood, & D´zatko, 2009). Att stimulera barns morfologiska medvetenhet kan exempelvis göras genom att analysera sammansatta ord eller genom att identifiera, ta bort och lägga till stavelser i ord (Vetenskapsrådet, 2015).…”
Section: Faktorer Av Betydelse För Läs-och Skrivutvecklingenunclassified